Media relations for school promotions at Trensains Muhammadiyah Sragen Senior High School - Fajar Junaedi; Budi Dwi Arifianto; Muhammad Rifki Ihsan Tamimi (Community Empowerment, 2023)
Trensains Muhammadiyah Sragen High School is a prominent Muhammadiyah institution located in Sragen, Central Java, known for its excellence in the field of science. The main challenge it faces is the lack of exposure in mass media due to its limited connection with the media. To address this issue, this community service program aims to enhance the media relations skills of the teachers at Trensains Muhammadiyah Sragen High School. This program was implemented through a workshop that involved the teachers from Trensains Muhammadiyah Sragen High School. The workshop covered topics such as media relations for school publications, news release writing, and the distribution of news releases to mass media outlets. As a result of this program, the teachers have improved their skills in creating news releases, leading to increased media coverage of Trensains Muhammadiyah Sragen High School across various platforms.